Doping study of two-well resonant-phonon terahertz quantum cascade lasers part I: doping profile dependence. (1st March 2023) - Miyoshi, Teppei; Wang, Kai Xi (Cathy); Lin, Tsung-Tse
Abstract: The influence of impurity doping on GaAs-based two-well resonant-phonon terahertz quantum cascade lasers is investigated theoretically, and efficient doping schemes are discussed. By using the rate equation model, the impacts of dopant amount, position, and distribution on the performance of a high-performance device is simulated focusing on a single module. The calculated optical gain is found to have a peak over the range of sheet doping density from 1.0 × 10 10 to 1.0 × 10 12 cm −2 in all eight doping conditions examined in this work. Among these patterns, the devices with the undoped condition and homogeneous-doping in phonon-wells mark high optical gain, and the latter is also resistant against the detuning of subband alignment due to band-bending under the high doping conditions. Furthermore, based on the simulation results, a modulation doping scheme whose active cores include both doped and undoped modules is suggested and discussed.